2021
DOI: 10.1186/s12974-021-02288-8
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of vascular adhesion protein 1 protects dopamine neurons from the effects of acute inflammation and restores habit learning in the striatum

Abstract: Background Changes in dopaminergic neural function can be induced by an acute inflammatory state that, by altering the integrity of the neurovasculature, induces neuronal stress, cell death and causes functional deficits. Effectively blocking these effects of inflammation could, therefore, reduce both neuronal and functional decline. To test this hypothesis, we inhibited vascular adhesion protein 1 (VAP-1), a membrane-bound protein expressed on the endothelial cell surface, that mediates leukoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 122 publications
2
8
0
Order By: Relevance
“…We then investigated the influence of neuroinflammation in the Pf, induced by the infusion of LPS, on AO encoding. We found that LPS caused considerable changes in Pf and degeneration of the thalamostriatal pathway, similar to that we found in the case of dopamine neurons when infused into the substantia nigra (47). However, it did not affect initial AO encoding and only abolished the ability of rats to encode AO associations after AO associations changed during outcome identity reversal, as we found previously after NMDA lesions of the Pf (6,7).…”
Section: Discussionsupporting
confidence: 88%
“…We then investigated the influence of neuroinflammation in the Pf, induced by the infusion of LPS, on AO encoding. We found that LPS caused considerable changes in Pf and degeneration of the thalamostriatal pathway, similar to that we found in the case of dopamine neurons when infused into the substantia nigra (47). However, it did not affect initial AO encoding and only abolished the ability of rats to encode AO associations after AO associations changed during outcome identity reversal, as we found previously after NMDA lesions of the Pf (6,7).…”
Section: Discussionsupporting
confidence: 88%
“…We then investigated the influence of neuroinflammation in the Pf, induced by the infusion of LPS, on AO encoding. We found that LPS caused considerable changes in Pf and degeneration of the thalamostriatal pathway, similar to that we found in the case of dopamine neurons when infused into the substantia nigra (46). However, it did not affect initial AO encoding and only abolished the ability of rats to encode AO associations after AO associations changed during outcome identity reversal, as we found previously after NMDA lesions of the Pf (4,5).…”
Section: Discussionsupporting
confidence: 88%
“…It has been reported that stereotactic injection of LPS into the brain can induce microglial activation, the release of a variety of pro-inflammatory mediators, and cognition dysfunction, which has become the common approach for modeling neuroinflammation in vivo [ 49 , 50 ]. To further verify the inflammation-tropism efficiency in AD characteristic lesions, an in vivo local inflammation model was established by stereotactic injection of LPS into the right hippocampus of C57BL/6J mice, followed by intranasal administration of DiL-labeled OT-Lipo@M and OT-Lipo, respectively ( Fig.…”
Section: Resultsmentioning
confidence: 99%